Implications of normal and disordered remodeling dynamics of corneodesmosomes in stratum corneum - Yasuo Kitajima (Wolters Kluwer Medknow Publications, 2015)
Desmosomes and corneodesmosomes are the most important adhering junctions, providing strength for the epidermal sheet structure made of living keratinocytes and enucleated stratum corneum corneocytes, respectively. These junctions are connected directly with transmembrane desmosomal cadherins, desmogleins (Dsgs), and desmocollins (Dscs); mainly Dsg1/Dsc1 and Dsg3/Dsc3 in desmosomes, and Dsg1/Dsc1 with corneodesmosin in corneodesmosomes. Dsgs and Dscs are associated with several proteins at their inner cytoplasmic domains to anchor keratin intermediate filaments. Desmosomes are not static, but dynamic units that undergo regular remodeling to allow for keratinocyte outward-migration in the epidermis. In corneodesmosomes, this dynamic nature of desmosomes is lost by fixing desmosomal cadherins with corneodesmosin at the intercellular domain of desmosomes and possibly with the formation of peptide bonds by activation of transglutaminase-1 at the intracellular face of desmosomes. Immediately after formation, corneodesmosomes normally commit to degradation, which is complicatedly regulated by proteolytic cleavage of their respective extracellular portions, via kallikrein-regulated peptidases and cathepsins. This proteolytic activity is in turn controlled by a variety of inhibitory agents, including protease inhibitors, cholesterol sulfate, and an acidic gradient. The impairment of protease control causes keratinization disorders. This review focuses on the regulation of corneodesmosome remodeling in relation to disorders of the stratum corneum.